2017
DOI: 10.2967/jnumed.116.189233
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual Comparison of 18F-PSMA-1007 PET/CT, Multiparametric MRI, and Radical Prostatectomy Specimens in Patients with Primary Prostate Cancer: A Retrospective, Proof-of-Concept Study

Abstract: Ga-prostate-specific membrane antigen (PSMA)-11 PET/CT represents an advanced method for the staging of primary prostate cancer (PCa) and diagnosis of recurrent or metastatic PCa. However, because of the narrow availability of Ga the development of alternative tracers is of high interest. The objective of this study was to examine the value of the new PET tracerF-PSMA-1007 for the staging of local disease by comparing it with multiparametric MRI (mpMRI) and radical prostatectomy (RP) histopathology. In 2016,F-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
118
4
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(132 citation statements)
references
References 33 publications
(61 reference statements)
8
118
4
2
Order By: Relevance
“…Several other series have evaluated the ability of PSMA‐PET and mpMRI to detect intra‐prostatic PCa. These series differ in methods and/or patient populations, therefore, no direct comparison can be made between the diagnostic accuracy of PSMA‐PET observed in the present results and that observed in these previous series .…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Several other series have evaluated the ability of PSMA‐PET and mpMRI to detect intra‐prostatic PCa. These series differ in methods and/or patient populations, therefore, no direct comparison can be made between the diagnostic accuracy of PSMA‐PET observed in the present results and that observed in these previous series .…”
Section: Discussioncontrasting
confidence: 64%
“…This approach may have biased the statistics for both PSMA‐PET and mpMRI (more segments classified as true positive or negative); therefore, we clustered our data; that is, we evaluated the diagnostic accuracy per patient by clustering all the segments of a prostate that belonged to one patient (Table ), and found that the results did not differ. Nonetheless, given the potential bias of a segmental analysis, we make no statement regarding the screening capabilities of the individual techniques, nor have we compared the diagnostic accuracy of our PSMA‐PET results with those of other published series , but have merely used this approach to compare PSMA‐PET and mpMRI in a surgical cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical trials have demonstrated the potential of [ 18 F]PSMA‐1007 as an attractive radiolabeled tracer for PC PET imaging . One clear advantage of [ 18 F]PSMA‐1007 is the non‐urinary excretion, which can benefit clinical decision making in local recurrence . Here, we describe the implementation and optimization of the recently published one‐step radiosynthesis of [ 18 F]PSMA‐1007 using commercially available modules …”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] One clear advantage of [ 18 F] PSMA-1007 is the non-urinary excretion, which can benefit clinical decision making in local recurrence. 12,[16][17][18] Here, we describe the implementation and optimization of the recently published one-step radiosynthesis of [ 18 F]PSMA-1007 using commercially available modules. 19…”
Section: Introductionmentioning
confidence: 99%